OPTIMALISASI PENCARIAN APOTEK TERDEKAT DENGAN METODE LOCATION BASED SERVICE PADA APLIKASI PERANGKAT BERGERAK - Hanggraini Dea Astuti; Zaky, Umar (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The development of information technology today is an important factor for the advancement of the times. Information technology has made significant contributions across various sectors, including the pharmaceutical field. This technology enables the public to access healthcare services more easily, particularly in terms of finding pharmacies. However, the large number of pharmacies in certain areas often makes it difficult for people to determine which pharmacy is the closest and offers the required medication, especially for prescription-only drugs and controlled substances. This situation can complicate matters, especially when medication is urgently needed. Therefore, this study aims to assist the public in locating the nearest pharmacies that provide the required medications while also reducing the time needed to fill prescriptions. The application developed utilizes Location-Based Service (LBS) technology to automatically determine pharmacy locations based on the user’s position. The application is equipped with key features such as user registration, pharmacy search, and prescription scanning. Based on testing using the blackbox method, the application has proven to function as expected. With this application, it is hoped that the public can more efficiently find pharmacies that meet their needs, making the prescription-filling process faster and more convenient